What is an Academic Journey [Marks, Interpretations, and Objects]?: Reflections by the Theories of Charles Sanders Peirce - Pradita, Yola; Bumen, Eko Julianto Krismanuel R.; Lelunu, Sapta; Manuputty, Juan Andika; Wardiannata, Evan (Lingua : Journal of Linguistics and Language, 2023)
The aim of this study is to investigate the extent to which Charles Sanders Peirce's ideas are based on prior research. Peirce's experiences are analysed as signifiers and signs in his text analysis. This research is a literature review that incorporates data from books and journals published within the last decade. This literature review analyses previous studies that use the lens of Charles Sanders Peirce's thoughts. The review shows that many of the instruments that Peirce put forward had not been accommodated in previous studies. Many authors who discuss Peirce focus on the theory as a means of self-reflection and personal growth. However, Peirce's philosophy advocates for inclusive analyses that take into account the subject's point of view. Additionally, the results indicate that the signifier's impact extends beyond the physical form of signs to include their interpretation. This includes the quality, accompanying objects, and relationships between subjects or subject-objects, as well as historical events, characters, relevant and balanced laws, and contextual habits.